Neutrophil extracellular traps and inflammatory response: Implications for the immunopathogenesis of ankylosing spondylitis - Zambrano‐Zaragoza, José Francisco; Gutiérrez‐Franco, Jorge; Durán‐Avelar, Ma. de Jesús; Vibanco‐Pérez, Norberto; Ortiz‐Martínez, Liliana; Ayón‐Pérez, Miriam Fabiola; Vázquez‐Reyes, Alejandro; Agraz‐Cibrián, Juan Manuel (International journal of rheumatic diseases, 2021)
Aim Ankylosing spondylitis (AS) pathogenesis has focused on the adaptive immune response; however, innate immune responses may also play a role in the inflammatory response of AS. Dysregulated neutrophil activation can induce tissue damage and contribute to the pathogenesis of immune‐related diseases. Hence, the aim of this study was to assess the effect of immune complexes formed with the p30 of Salmonella typhimurium and anti‐p30 antibodies present in the sera of AS patients and controls in inducing the release of neutrophil extracellular traps (NETs) and the secretion of pro‐inflammatory cytokines. Methods We collected polymorphonuclear leukocytes (PMNs) from healthy donors. The PMNs isolated were stimulated with p30 alone or in immunocomplexes formed with antibodies presents in sera of AS patients or control subjects. Then, the NETs were analyzed by fluorescence microscopy. Concentrations of interleukin (IL)‐6, tumor necrosis factor (TNF)‐α, IL‐1β, IL‐8 and IL‐10, were determined using the Cytometric Bead Array kit. Results Significant difference was observed in the release of NETs between the neutrophils stimulated with p30 + AS (70.52 ± 16.24) those unstimulated neutrophils (9.94 ± 12.12; P = .0095), stimulated with phorbol 12‐myristate 13‐acetate (39.78 ± 14.50; P = .0190), stimulated with control serum (CS) (10.85 ± 5.33; P = .0082) and serum of AS patient (10.28 ± 6.15; P = .0087). The stimulation of neutrophils with p30 alone induced a relatively low production of IL‐6 (64.5 pg/mL), IL‐8 (2658.3 pg/mL), IL‐1β (31.11 pg/mL), and TNF‐α (3.8 pg/mL), compared to p30 + AS and p30 + CS groups. Conclusion Our results show that neutrophils release NETs and pro‐inflammatory cytokines in response to p30 in immunocomplexes. These findings could improve our understanding of the role of innate immunity in the initiation and/or maintenance of inflammatory responses, and in the progression of AS.